ON THE DIRECTIONS OF CUSTOMS POLICY IMPROVEMENT AND MECHANISMS OF INNOVATIVE DEVELOPMENT OF CUSTOMS AFFAIRS - PASHKO, Pavlo; PASHKO, Dalyana; CHUMAK, Oksana; MYROSHNYCHENKO, Ganna; SHTYK, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article presents the results of the author's research on the system of guarantee obligations when importing goods to the US territory, the elements of which can be used in the system of providing customs revenues to the State Budget of Ukraine. The authors highlight the importance of implementing a guarantee system to reduce risks and accelerate customs procedures. The EU’s Customs Blueprints are presented as a tool to simultaneously lower costs and enhance control efficiency while ensuring the security of supply chains. The introduction of financial guarantees in customs procedures is noted as a way to minimize the risk of tax shortfalls. The article also emphasizes international experience, such as the U.S. approach, where guarantees are based on companies' tax payment obligations. Legislative changes to Ukraine’s Customs Code, aligned with EU law, reflect the country’s commitment to simplifying customs procedures and ensuring economic security. The conclusion stresses the need for modern technologies like electronic tracking systems to strengthen customs control and improve administrative efficiency in Ukraine.
Keywords: customs policy; сustoms; сustoms business; EU; customs regulation; foreign trade operations; mechanisms of development; guarantees; planning